2022
DOI: 10.7759/cureus.31807
|View full text |Cite
|
Sign up to set email alerts
|

Charlson Comorbidity Index as a Predictor of Difficult Cholecystectomy in Patients With Acute Cholecystitis

Abstract: BackgroundThe Charlson Comorbidity Index (CCI) has been validated as a predictor of overall survival and post-surgical mortality. CCI is adopted by Tokyo Guidelines as one of the main criteria in the management of acute cholecystitis. Our study evaluates the role of CCI in predicting difficult cholecystectomy. MethodsAll patients who underwent cholecystectomy for acute cholecystitis between January 2017 and September 2019 were included. CCI, Emergency Surgery Score (ESS), and American Society of Anesthesiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Additionally, intervention with endoscopic methods has been recommended for these patient groups. In the patient group with acute cholecystitis, which is another risky surgery requirement and CCI determines the risk of preoperative mortality, complications were more common in those with CCI>6 [37]. Satheakeerthy et al found the median CCI score to be 4 in their study [38].…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, intervention with endoscopic methods has been recommended for these patient groups. In the patient group with acute cholecystitis, which is another risky surgery requirement and CCI determines the risk of preoperative mortality, complications were more common in those with CCI>6 [37]. Satheakeerthy et al found the median CCI score to be 4 in their study [38].…”
Section: Discussionmentioning
confidence: 92%